Point-slope form of equation is: ![y - 7 = -15(x-1)](https://tex.z-dn.net/?f=y%20-%207%20%3D%20-15%28x-1%29)
Step-by-step explanation:
Given points are:
(2,-8) and (1,7)
First of all we have to calculate the slope of the line
so,
![m=\frac{y_2-y_1}{x_2-x_1}\\= \frac{7-(-8)}{1-2}\\=\frac{7+8}{-1}\\=\frac{15}{-1}\\= -15](https://tex.z-dn.net/?f=m%3D%5Cfrac%7By_2-y_1%7D%7Bx_2-x_1%7D%5C%5C%3D%20%5Cfrac%7B7-%28-8%29%7D%7B1-2%7D%5C%5C%3D%5Cfrac%7B7%2B8%7D%7B-1%7D%5C%5C%3D%5Cfrac%7B15%7D%7B-1%7D%5C%5C%3D%20-15)
Point-slope form is given by:
![y-y_1 = m(x-x_1)](https://tex.z-dn.net/?f=y-y_1%20%3D%20m%28x-x_1%29)
Putting the value of slope
![y-y_1 = -15(x-x_1)](https://tex.z-dn.net/?f=y-y_1%20%3D%20-15%28x-x_1%29)
We can put any one of two given points in the equation to find the final form of point-slope form
So
Putting (1,7) in the equation
![y - 7 = -15(x-1)](https://tex.z-dn.net/?f=y%20-%207%20%3D%20-15%28x-1%29)
Hence, point-slope form of equation is: ![y - 7 = -15(x-1)](https://tex.z-dn.net/?f=y%20-%207%20%3D%20-15%28x-1%29)
Reducing and simplifying
![y - 7 = -15(x-1)\\y-7 = -15x+15\\y-7+7 =-15x+15-7\\y = -15x+8\\15x+y = 8](https://tex.z-dn.net/?f=y%20-%207%20%3D%20-15%28x-1%29%5C%5Cy-7%20%3D%20-15x%2B15%5C%5Cy-7%2B7%20%3D-15x%2B15-7%5C%5Cy%20%3D%20-15x%2B8%5C%5C15x%2By%20%3D%208)
Keywords: Point-slope form, equation of line
Learn more about equation of line at:
#LearnwithBrainly
Answer:
PART 2,4,6 are not solvable since they do not have any number
Part 1
1 = 61
2 = 119
3 = 61
4 = 119
5 = 61
6 = 119
7 = 61
8 = 119
Part 3
1 = 128
2 = 52
3 = 128
4= 52
5 = 128
6 =52
7 = 128
8 =52
Part 5
1 = 135
2 = 45
3 = 135
4 = 45
5= 135
6= 45
7=135
8= 45
Answer:
![67\frac{23}{28}](https://tex.z-dn.net/?f=67%5Cfrac%7B23%7D%7B28%7D)
Step-by-step explanation:
![36-\left[100\div \:560-32\left(8\div \:4-1\right)\right]\\\\100\div \:560-32\left(8\div \:4-1\right)\\\\=100\div \:560-32\cdot \:1\\\\=\frac{100}{560}-32\cdot \:1\\\\=\frac{100}{560}-32\\\\=-\frac{891}{28}\\\\\\=36-\left(-\frac{891}{28}\right)\\\\36-\left(-\frac{891}{28}\right)\\\\=36+\frac{891}{28}\\\\\frac{36\cdot \:28}{28}+\frac{891}{28}\\\\\frac{36\cdot \:28+891}{28}\\\\=\frac{1899}{28}\\\\\\\frac{1899}{28}(1899\div28)=67\frac{23}{28}](https://tex.z-dn.net/?f=36-%5Cleft%5B100%5Cdiv%20%5C%3A560-32%5Cleft%288%5Cdiv%20%5C%3A4-1%5Cright%29%5Cright%5D%5C%5C%5C%5C100%5Cdiv%20%5C%3A560-32%5Cleft%288%5Cdiv%20%5C%3A4-1%5Cright%29%5C%5C%5C%5C%3D100%5Cdiv%20%5C%3A560-32%5Ccdot%20%5C%3A1%5C%5C%5C%5C%3D%5Cfrac%7B100%7D%7B560%7D-32%5Ccdot%20%5C%3A1%5C%5C%5C%5C%3D%5Cfrac%7B100%7D%7B560%7D-32%5C%5C%5C%5C%3D-%5Cfrac%7B891%7D%7B28%7D%5C%5C%5C%5C%5C%5C%3D36-%5Cleft%28-%5Cfrac%7B891%7D%7B28%7D%5Cright%29%5C%5C%5C%5C36-%5Cleft%28-%5Cfrac%7B891%7D%7B28%7D%5Cright%29%5C%5C%5C%5C%3D36%2B%5Cfrac%7B891%7D%7B28%7D%5C%5C%5C%5C%5Cfrac%7B36%5Ccdot%20%5C%3A28%7D%7B28%7D%2B%5Cfrac%7B891%7D%7B28%7D%5C%5C%5C%5C%5Cfrac%7B36%5Ccdot%20%5C%3A28%2B891%7D%7B28%7D%5C%5C%5C%5C%3D%5Cfrac%7B1899%7D%7B28%7D%5C%5C%5C%5C%5C%5C%5Cfrac%7B1899%7D%7B28%7D%281899%5Cdiv28%29%3D67%5Cfrac%7B23%7D%7B28%7D)
Answer:
The answer is ![6\frac{5}{8}](https://tex.z-dn.net/?f=6%5Cfrac%7B5%7D%7B8%7D)
Step-by-step explanation:
-12 pounds + ![5\frac{3}{8}](https://tex.z-dn.net/?f=5%5Cfrac%7B3%7D%7B8%7D)
-12+![5\frac{3}{8}](https://tex.z-dn.net/?f=5%5Cfrac%7B3%7D%7B8%7D)
=-12+5+![\frac{3}{8}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B8%7D)
=(-12+5)+![\frac{3}{8}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B8%7D)
=(-7)+![\frac{3}{8\\}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B8%5C%5C%7D)
=![-6\frac{5}{8}](https://tex.z-dn.net/?f=-6%5Cfrac%7B5%7D%7B8%7D)
Mr.Yoo's weight dropped by ![6\frac{5}{8}](https://tex.z-dn.net/?f=6%5Cfrac%7B5%7D%7B8%7D)